PENEGAKAN HUKUM TINDAK PIDANA PENIPUAN INVESTASI SKEMA PIRAMIDA DI PASAR MODAL - Maulana, Wahyu; Multiwijaya, Vience Ratna; Suar, Aprima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Investment fraud through pyramid schemes in the capital market has become an increasingly pressing issue as public interest in investments, especially in the form of cryptocurrency, rises. This study aims to examine the legal regulations related to investment fraud crimes and the application of criminal sanctions against the perpetrators. First, legal regulations in Indonesia regarding investment fraud, particularly pyramid schemes, still face serious challenges despite the existence of regulations such as the Capital Market Law and Bappebti Regulation No. 7 of 2020. These fraudulent practices, often caused by a lack of investor understanding of investment risks, are regulated under Article 378 of the Indonesian Penal Code (KUHP). Second, the enforcement of law against these fraud perpetrators is crucial for maintaining public trust and market stability. The applicable criminal sanctions include a maximum prison sentence of 1 year and 4 months for individuals, as well as fines or business closures for legal entities, according to the provisions of the KUHP. Although a legal framework exists, challenges in proving cases and the complexities of the technology used in pyramid schemes remain obstacles to law enforcement. This study provides a better understanding of the challenges in enforcing laws against investment fraud in pyramid schemes in the capital market and emphasizes the need for increased education for investors.Keywords: Law enforcement, criminal acts, investment fraud, pyramid schemes, capital market.